PO.5.108 Combined model of renal histopathology and clinical parameters better predicts one-year renal outcomes in lupus nephritis: analysis of 334 kidney biopsies. (27th September 2022) - Gopal, A; Kavadichanda, C; Bairwa, D; Shah, S; Bh, S; Mehra, S; Thabah, M; Negi, V
Abstract : Background/Purpose: Diagnosis of Lupus Nephritis (LN) is currently based on laboratory tests and renal histopathology. The role of histopathological features in determining long term outcomes is unclear. The objectives are to determine if clinical and biochemical parameters at baseline could identify renal histopathological class and to assess the clinico-histopathological predictors of renal response. Methods: This is a single centre retrospective study comprising 334 LN renal biopsies. Clinical and biochemical parameters at the time of biopsy were noted and their association with histopathological class, activity and chronicity scores (AS/CS) (ISN/RPS classification) were evaluated. Complete, partial or no response(CR, PR, NR) for the renal outcome (EULAR/EDTA) at 1 year were calculated for 293 patients. Binary logistic regression was done to look for the predictors of NR. Results: Class III/IV LN was seen in 240(71.8%). Hypertension was seen in (52.1%) of class III/IV and <25% each with class II, V and combined class(p<0.001). Class III/IV had lower eGFR [87.6(62.75–118.8)] (p<0.001) than the other classes. Nephrotic range proteinuria was seen in 32% of class V and 21% in class III/IV (p=0.004) Among class-III/IV AS had weak correlation with baseline UPCR (r=0.31) and eGFR (r=-0.172) (p<0.01). CS had weak negative correlation with eGFR (r=-0.212, p<0.01). NR at 1 year was higher in males (OR-4.6, 95%CI-1.9–10.8, p<0.001), those with abnormal serum creatinine (OR-3.3, 95%:CI1.6–7.02, p-0.001), higher renal SLEDAI (p<0.05), higher AS, CS (p<0.001), interstitial inflammation and tubular atrophy(p<0.005) (Table-1). On binary logistic regression a combined clinico-histopathological model comprising of serum creatinine, UPCR, male sex and CS performed best in predicting NR ( figure 1 ). Conclusion: Clinical and biochemical parameters can predict the renal histological class to a fair extent but have limited value in predicting the activity and chronicity parameters. Since a combination of clinical and histopathology parameters are better in predicting renal outcomes, performing renal biopsies should be encouraged in LN.